2015
DOI: 10.1111/cei.12627
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CXCL-1: activity in the vitreous during proliferative vitreoretinopathy

Abstract: SummaryThe aim of this study was to investigate CXCL-1 chemokine levels in the vitreous during rhegmatogenous retinal detachment (RRD) with and without proliferative vitreoretinopathy (PVR) and identify possible correlations with clinical parameters (extent and duration or RRD and PVR grade). Vitreous samples from patients with primary RRD with or without PVR were collected and assayed using a double antibody enzymelinked immunosorbent assay (ELISA). Eleven vitreous samples from organ donors were employed as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Several studies have documented elevated levels of cytokines and growth factors in the vitreous of RD patients. 7 13 Transcriptomic analysis following RD in porcine and human retinas found that inflammatory genes dominated the response. 14 , 15 Experimental models of RD exhibit increased cytokine expression, gliosis, microgliosis, and subretinal infiltration of monocytes/macrophages.…”
mentioning
confidence: 99%
“…Several studies have documented elevated levels of cytokines and growth factors in the vitreous of RD patients. 7 13 Transcriptomic analysis following RD in porcine and human retinas found that inflammatory genes dominated the response. 14 , 15 Experimental models of RD exhibit increased cytokine expression, gliosis, microgliosis, and subretinal infiltration of monocytes/macrophages.…”
mentioning
confidence: 99%
“…In the retina, it has been demonstrated that CXCL1 levels correlated significantly with the duration of RD and PVR 23 . Increased CXCL1 levels may be indicative of mild inflammation in the detached retina and the adjacent vitreous 24 . In this study, sublethal dose of H 2 O 2 alone upregulated CXCL1 protein in culture media of ARPE-19 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also focused on CXCL-1 levels that have been found to be significantly elevated in cases of RRD [29, 30, 33], while maximum concentration coincided with total RRD, long duration, and late stage of PVR [30]. RPE cells have been shown to produce CXCL-1 as a result of PVR-related mediators.…”
Section: Analysis Of Inflammatory Immune Mediatorsmentioning
confidence: 99%
“…Abundant evidence is available showing that the innate immune responses and the presence of inflammatory mediators in ocular tissue may underlie the pathologic changes that ultimately lead to development of proliferative vitreoretinopathy (PVR) [24‒46]. PVR is the most common cause for RRD recurrence and postoperative visual impairment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation